2008
DOI: 10.1584/jpestics.g07-28
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating and blocking actions of neonicotinoids on the response to acetylcholine of the neuronal .ALPHA.4.BETA.2 nicotinic acetylcholine receptor

Abstract: Effects of imidacloprid, clothianidin, thiacloprid and related compounds on the acetylcholine (ACh)-induced response of the recombinant, expressed chicken a4b 2 nicotinic acetylcholine receptor (nAChR) were investigated using voltage-clamp electrophysiology. Imidacloprid and clothianidin enhanced the amplitude of the response to ACh of a4b 2 nAChR. In complete contrast, thiacloprid attenuated the amplitude of the response to ACh of a4b 2 nAChR. Replacing the nitro group of imidacloprid by a cyano group abolish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…26,27) Furthermore, recent electrophysiological experiments have indicated that the cyano group of thiacloprid may have unique interactions as compared with the nitro group of imidacloprid. 29) Accordingly, the different effects of acetamiprid and imidacloprid, as indicated by the pEC 50 values, are probably due to their slightly dif-ferent interactions with aphid nAChRs.…”
Section: Discussionmentioning
confidence: 98%
“…26,27) Furthermore, recent electrophysiological experiments have indicated that the cyano group of thiacloprid may have unique interactions as compared with the nitro group of imidacloprid. 29) Accordingly, the different effects of acetamiprid and imidacloprid, as indicated by the pEC 50 values, are probably due to their slightly dif-ferent interactions with aphid nAChRs.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, binding studies reveal that imidacloprid and the parent compounds bound with very low affinities to the rat brain membranes and neuronal α7 and α4β2 nAChRs (Kagabu et al, ; Lansdell and Millar, ). Moreover, currents elicited by ACh are differently potentiated by clothianidin and imidacloprid suggesting that the effects of neonicotinoids on ACh‐induced currents could be dependent on the chemical structure of neonicotinoids (Toshima et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…IMI is similarly ineffective on recombinant chick α7 and α4β2 receptors expressed in Xenopus oocytes, with the concentration–effect curves placed at concentrations exceeding that for ACh by up to two orders of magnitude (Matsuda et al,1998; Ihara et al,2003). A previous study showed that currents elicited by ACh from chick α4β2 receptors can be potentiated by CTD and IMI (Toshima et al,2008).…”
mentioning
confidence: 99%